Study on a Novel High-Efficiency Bridgeless PFC Converter - Cao Taiqiang; Chen Zhangyong; Wang Jun; Sun Zhang; Luo Qian; Zhang Fei (Journal of Applied Mathematics)
In order to implement a high-efficiency bridgeless power factor correction converter, a new topology and operation principles of continuous conduction mode (CCM) and DC steady-state character of the converter are analyzed, which show that the converter not only has bipolar-gain characteristic but also has the same characteristic as the traditional Boost converter, while the voltage transfer ratio is not related with the resonant branch parameters and switching frequency. Based on the above topology, a novel bridgeless Bipolar-Gain Pseudo-Boost PFC converter is proposed. With this converter, the diode rectifier bridge of traditional AC-DC converter is eliminated, and zero-current switching of fast recovery diode is achieved. Thus, the efficiency is improved. Next, we also propose the one-cycle control policy of this converter. Finally, experiments are provided to verify the accuracy and feasibility of the proposed converter.